2014
DOI: 10.3109/17538157.2013.872110
|View full text |Cite
|
Sign up to set email alerts
|

Information exchange between registered nurses and district nurses during the discharge planning process: cross-sectional analysis of survey data

Abstract: Objectives: Discharge planning is an important care process for managing transitions from the hospital to the community. It has been studied for >20 years, but few studies clarify the information exchanged between healthcare providers. This study aimed to describe nurses' experiences and perceptions of information exchange during the discharge planning process, focused on what, when and how information is exchanged between the hospital and primary healthcare. Method: A web-based census survey was used to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Nurses have expressed concerns regarding the potential risks related to the management of personal records . One study found the information on one patient reported by a caregiver via an ICT to be insufficient , potentially impacting safety. This review also found that nurses believed that ICT could improve the quality and uniformity of care services .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses have expressed concerns regarding the potential risks related to the management of personal records . One study found the information on one patient reported by a caregiver via an ICT to be insufficient , potentially impacting safety. This review also found that nurses believed that ICT could improve the quality and uniformity of care services .…”
Section: Resultsmentioning
confidence: 99%
“…ICT in nursing practice offers advantages for nurses’ working situations. ICT use can, for example, save time , facilitate information exchange on nonacute or unmodified actions and short‐circuit nurses’ assessments of patients . For some nurses, ICT use has improved their work environments by facilitating collaboration between nurses and colleagues both within wards and between units .…”
Section: Resultsmentioning
confidence: 99%
“…Contact nurses in the community are responsible for coordinating the continuation of home care of people with chronic illness after hospital discharge. In an aging population, the number of chronically ill patients increases, hospital stays shorten, and the quantity of hospital beds decreases, making information exchange very relevant for discharge planning and home care [25]. Hence, as the main professionals involved in the process of discharge, community nurses need to cooperate with health and non-health professionals in order to develop, improve, and redesign community services [26].…”
Section: Discussionmentioning
confidence: 99%
“…An interview study made as a first part of this study about the implementation process using video conferencing in comprehensive discharge planning mentions a lack of respect, between the professionals and for each other's competence, as a factor that has a negative impact on discharge planning [5]. Also difficulty addressing communication between professions involved in the planning session is described as a problem in a survey study from Sweden [7], as well as in a comparative study based on data from Sweden and the UK [6]. Qualitative studies from Hong Kong, the UK and Ireland also describe communication problems as a barrier to improving the discharge planning process [8][9][10], along with lack of co-ordination of the discharge process, resources and time [9,10].…”
Section: Introductionmentioning
confidence: 99%